Water soluble vitamin needs of weaned pigs - M D Newcomb; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1985)
Two trials, using 360 pigs weaned at 17-27 days, were conducted to evaluate pig performance as affected by the addition of folic acid, thiamin, biotin, pyridoxine, or ascorbic acid to the diet. Combined data from Trial I and Trial II indicated that adding these supplemental vitamins did not improve daily gain or feed efficiency. These results suggest the addition of these supplemental water-soluble vitamins to a corn-soybean meal 20% whey diet or injection of a B-vitamin complex for pigs weaned at 3-4 weeks of age is not beneficial.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Water soluble vitamin; Weaned pigs